Persepsi Orangtua terhadap Pendidikan Anak Usia Dini - Dea Sita Pratiwi; Ajeng Ayu Widiastuti; Maria Melita Rahardjo (Satya Widya, 2018)
The purpose of this study was to find out how the parent's perception of early childhood education in RW 01 Dukuh Krajan, Salatiga. The design is descriptive quantitative with the subject of research that is parents who have children aged 3-5 years, amounting to 58 people. Data on parental perceptions are collected through a questionnaire and then will be classified according to the level of parental education, income level of parents, parents who have sent their children and parents who have not send their children to school in early childhood. The result of questionnaire of parents perception in level of education S1 and S2 in good category (50%), SMA / SMK is in Good category (36,11%) and SMP is in Enough category (50%). The calculation of the value of the questionnaire according to the parent's income level (a) in the category of Good (33.33%) and Less (33.33%), income (b) is in Good category (41.67%) and income ( c) is in the category of Very Good (57.14%). Then based on parents who have sent their children to school is in Good category (52,38%), perception of parents who have not yet send their child to PAUD is in Enough category (37,84%).